Actionable points in SDG 5 for eradicating gender based violence By year 2030 in Nigeria: Way forward - Ogunlade, Ibiyinka (Corpus Intellectual, 2023)
The major challenge facing gender parity and discrimination in developing countries such as Nigeria is acts of various forms of abuse against females. Hence, workable strategies to eradicate genderbased violence (GBV) become imperative and essential towards an effort to achieve gender equality and empower women and girls (SDG 5). This study provides a brief overview of the types of GBV with rape and human trafficking turning out to be more prominent as a result of economic crisis, unemployment and massive exploitation, with visible physical and emotional signs displayed by victims. The astronomical rate of increase of GBV because of the prevalent issues such as, male dominance system of the society, joblessness and uneven access to education among other factors in Nigeria has widened the gender gap. The 6 targets of SDG5 that are outcome-oriented are highlighted with intervention programmes by the United Nations and its partners in the country. It is hoped that by the year 2030 the goals of Sustainable Development Agenda in achieving poverty and hunger reduction, provision of quality healthcare and promotion of well-being, ensuring quality education, promote gender equality and empower women and girls, safeguard the environment and its natural resources, provide decent work and economic growth, among other targets in creating an egalitarian society. Existing gender policies, guidelines and legal frameworks such as Violence Against Person Prohibition Acts (VAPP) 2015, Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and Domestic Violence laws are presented with recommendations of preventive and control measures of Gender based violence.